Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

We introduced generalized eigenvectors and then we were given this example:

Given an endomorphism $\varphi: V \to V$ with $\chi_\varphi(t) = (-1)^n (t-\lambda)^n$, then $U(\lambda) = V$ since $(\varphi-\lambda · \mathrm{id})^n = 0$.

I don't really get this. Why is it that $(\varphi-\lambda · \mathrm{id})^n = 0$? If this is the case then clearly $U(\lambda) = V$ but I can't justify this.

share|cite|improve this question
up vote 1 down vote accepted

This is by the Cayley–Hamilton theorem: $0=\chi_\varphi(\varphi)=(-1)^n(\varphi-\lambda I)^n$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.